F2α-isoprostane, Na+-K+ ATPase and membrane fluidity of placental syncytiotrophoblast cell in preeclamptic women with vitamin E supplementation (Faculty of Medicine Universitas Indonesia, 2012)
Background: The aim of our study was to analyze F2α-isoprostane level, Na+-K+ ATPase activity and placental syncytiotrophoblast cell membrane fluidity in preeclamptic women who received vitamin E supplementation. Methods: The study was conducted between September 2003 and February 2005 at Budi Kemuliaan Maternity Hospital, Central Jakarta. Samples were 6 preeclamptic women with vitamin E supplementation, 6 preeclamptic women without vitamin E supplementation and 6 normal pregnant women. The dose of vitamin E was 200 mg daily. F2α-isoprostane was measured with ELISA reader at λ of 450 nm. Cell membrane fluidity was measured by comparing the molar ratio of total cholesterol and cell membrane phospholipid concentration. The cholesterol was measured by Modular C800 using Roche reagent. Phospholipid was measured by Shimadzu RF5301PC spectrofluorometer (excitation 267 nm, emission 307 nm). Na+-K+ ATPase activity was inhibited by ouabain. Pi production was measured with Fiske and Subbarow method using spectrophotometer at λ of 660 nm. Data was analyzed using F test with one-way ANOVA. Results: Vitamin E supplementation in preeclamptic women decreased the oxidative stress, indicated by significantly lower level of F2α-isoprostane compared to those without vitamin E (26.72 ± 11.21 vs 41.85 ± 7.09 ng/mL, respectively, p = 0.017). Membrane fluidity in syncytiotrophoblast cell of preeclampsia with vitamin E group was maintained at 0.39 ± 0.08 while in those without vitamin E was 0.53 ± 0.14 (p = 0.04). Na+-K+ ATPase activity in syncytiotrophoblast cell membrane was not affected by vitamin E (p = 0.915). Conclusion: Vitamin E supplementation in preeclamptic women decreases F2α-isoprostane level and maintains cell membrane fluidity of syncytiotrophoblast cells; however, it does not increase Na+-K+ ATPase enzyme activity. (Med J Indones. 2012;21:225-9)